ChemInform Abstract: Palladium‐Catalyzed Migratory Insertion of Isocyanides: An Emerging Platform in Cross‐Coupling Chemistry. Issue 46 (24th October 2013) - Vlaar, Tjoestil; Ruijter, Eelco; Maes, Bert U. W.; Orru, Romano V. A.
Abstract Review: 20 refs.